Predicted changes in habitat suitability for human schistosomiasis intermediate host snails for modelled future climatic conditions in KwaZulu-Natal, South Africa - Nwoko, Onyekachi Esther; Manyangadze, Tawanda; Chimbari, Moses John (Frontiers in Environmental Science, 2023)
Climate change alters environmental and climatic conditions, leading to expansion or contraction and possible shifts in the geographical distribution of vectors that transmit diseases. Bulinus globosus and Biomphalaria pfeifferi are the intermediate host snails for human schistosomiasis in KwaZulu-Natal (KZN) province, South Africa. Using the Maximum entropy (MaxEnt) model, we modelled the current and future distribution of human schistosomiasis intermediate host snails in KZN using two representation concentration pathways (RCP4.5 and RCP8.5) for the year 2085. Thirteen and ten bioclimatic variables from AFRICLIM were used to model the habitat suitability for B. globosus and B. pfeifferi, respectively. The Jack-knife test was used to evaluate the importance of each bioclimatic variable. Mean temperature warmest quarter (BIO10, 37.6%), the number of dry months (dm, 32.6%), mean diurnal range in temperature (BIO2, 10.8%), isothermality (BIO3, 6.7%) were identified as the top four bioclimatic variables with significant contribution to the model for predicting the habitat suitability for B. globosus. Annual moisture index (mi, 34%), mean temperature warmest quarter (BIO10, 21.5%), isothermality (BIO3, 20.5%), and number of dry months (dm, 7%) were identified as the four important variables for the habitat suitability of B. pfeifferi. Area under the curve for the receiving operating characteristics was used to evaluate the performance of the model. The MaxEnt model obtained high AUC values of 0.791 and 0.896 for B. globosus and B. pfeifferi, respectively. Possible changes in the habitat suitability for B. globosus and B. pfeifferi were observed in the maps developed, indicating shrinkage and shifts in the habitat suitability of B. pfeifferi as 65.1% and 59.7% of the current suitable habitats may become unsuitable in the future under RCP4.5 and RCP8.5 climate scenarios.Conversely, an expansion in suitable habitats for B. globosus was predicted to be 32.4% and 69.3% under RCP4.5 and RCP8.5 climate scenarios, with some currently unsuitable habitats becoming suitable in the future. These habitat suitability predictions for human schistosomiasis intermediate host snails in KZN can be used as a reference for implementing long-term effective preventive and control strategies for schistosomiasis.